Outcomes of treatment of cats with effusive feline infectious peritonitis using parenterally administered remdesivir with two different maintenance dose concentrations - Ahmad Zaki ANWER; Mahmoud Saber ABDULKADER; Emil Saad ABDEL MASSIEH (Kafkas Universitesi Veteriner Fakültesi Dergisi)
The emergence of antiviral drugs against human coronavirus offers a promising approach for treating progressive and fatal feline infectious peritonitis (FIP). This study aims to evaluate the effectiveness of remdesivir in treating effusive FIP and to compare the lower and upper maintenance doses. Sixteen cats suffering from effusive FIP were randomly assigned to two treatment groups, eight cats in each group. Both groups (A) and (B) were treated with the same initial dose of 10-12 mg/kg body weight by IV route for the first 3 days, while for maintenance dose, group (A) was treated with a lower limit of 5-6 mg/ kg body weight and group (B) was treated with upper limit 10-12 mg/kg body weight by SC route till day 84. The overall survival rate was 87.5%. Two cats (one from each group) died within the first 48 h of the treatment protocol. The recurrence rate excluding the two dead cats was 14.28% for group A; one case had disease recurrence, while there was no case recurrence in group B; no significant difference was observed between the two treatment groups in recurrence rate (P<0.05). At the end of the treatment period, all 14 surviving cats had normalized clinicopathological findings and disease remission. The lower maintenance dose of remdesivir is as effective as the upper dose.